Stunting Incidence Determinants in Toddlers (24–59 Months) Born to Early Married Mothers - Anna Septina Andarini, I Wayan Agung Indrawan, Ariani (Pakistan Journal of Medical & Health Sciences, 2022)
In 2019, the prevalence of stunting in Indonesia was 27.67 %. With a 23 % stunting rate, Kediri ranked top in East Java in 2020. This study aimed to determine the stunting determinants in toddlers (24-59 months) born to early married mothers in Mojoroto District, Kediri City. This research is a descriptive-analytic study employing a cross-sectional design. A total of 61 mothers who married at an early age in the Mojoroto District constituted the sample. Purposive sampling approach. The significance value is less than 0.05 (sig < 0.05) for the effect of the independent variable on the dependent variable through the intervening variable, namely breast milk exclusion, education, nutritional status of pregnant women, and environmental sanitation, according to the results of multivariate research using the path test (path). The significance value for variables with no significant effect is more than 0.05 (sig > 0.05), including a history of infection, Nutrient Complementary Foods, socioeconomic status, occupation, age of delivery, low birth weight, and health services. Diverse sectors, particularly the health sector, pay close attention to women of reproductive age who marry early, focusing on their nutritional quality throughout pregnancy. Furthermore, efforts to discourage early marriage are enhanced.